Subsidiary knowledge flow strategies and purpose of expatriate assignments. Issue 3 (June 2019) - Cheong, Adeline; Sandhu, Manjit S.; Edwards, Ronald; Poon, Wai Ching
Abstract: Although a general association between the role of international assignees and knowledge transfer has been noted in the international human resource literature, very little is known on how subsidiary knowledge flow strategies influence the purpose of expatriate assignments. Building specifically on Gupta and Govindarajan's typology of subsidiary knowledge flow strategies and Hocking's expatriate assignment purpose, we examine the link between subsidiary knowledge flow and the purpose of expatriate assignments using a mixed method approach. Combining survey data and qualitative interviews from 156 subsidiaries in the service and manufacturing sector in Malaysia and Singapore, we find that subsidiaries with divergent strategic roles have different knowledge flow strategies, thus leading to different purposes of expatriate assignments.